2017
DOI: 10.1111/resp.13107
|View full text |Cite
|
Sign up to set email alerts
|

The overlaps of asthma or COPD with OSA: A focused review

Abstract: Asthma, chronic obstructive pulmonary disease (COPD) and obstructive sleep apnoea (OSA) are the most common respiratory disorders worldwide. Given demographic and environmental changes, prevalence for each is likely to increase. Although exact numbers are not known, based on chance alone, many people will be affected by both lower airways obstruction and concomitant upper airway obstruction during sleep. Some recent studies suggest that there is a reciprocal interaction, with chronic lung disease predisposing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 73 publications
(99 reference statements)
4
45
0
Order By: Relevance
“…The concurrence of OSA with various neurocognitive and mental health issues can worsen outcomes compared with experiencing either condition in isolation . Similar worsening of outcomes has been reported with the overlap of OSA and obstructive lung disease (overlap syndrome) . Improved cognition function with CPAP has been reported, particularly in vulnerable populations, while its use in overlap syndrome is associated with quality of life improvements, reduced hospitalizations and lower mortality …”
Section: Sleepsupporting
confidence: 61%
See 1 more Smart Citation
“…The concurrence of OSA with various neurocognitive and mental health issues can worsen outcomes compared with experiencing either condition in isolation . Similar worsening of outcomes has been reported with the overlap of OSA and obstructive lung disease (overlap syndrome) . Improved cognition function with CPAP has been reported, particularly in vulnerable populations, while its use in overlap syndrome is associated with quality of life improvements, reduced hospitalizations and lower mortality …”
Section: Sleepsupporting
confidence: 61%
“…Mounting evidence demonstrates the complex interactions between OSA and other co‐morbid conditions . These co‐morbidities affect healthcare utilization and are associated with poorer clinical outcomes .…”
Section: Sleepmentioning
confidence: 99%
“…Effects of asthma on OSA involves mechanical factors (increased airway resistance during REM sleep due to reduction in Functional Residual capacity and End Expiratory Lung Volume leading to upper airway collapse and worsening of apnea), Smoking (directly increasing airway edema and resistance), Corticosteroids use (causing airway myopathy, obesity and airway fat deposition) and increased nasal resistance due to rhinitis or polyps. Similarly, recent animal and human studies have shown OSA could influence lower airway inflammation and remodeling [22]. Effects of OSA on asthma includes increasing vagal tone during apneic episodes triggering muscarinic receptors induced bronchoconstriction, intermittent hypoxic oxidative stress causing endothelial dysfunction, increased inflammation, Vascular Endothelial Growth Factor (VEGFhypoxia-sensitive glycoprotein which may contribute to bronchial inflammation), Leptin-related airway changes (pro-inflammatory effects), Sleep fragmentation (causing increased cholinergic outflow during REM sleep), GERD (asthma triggered form microaspirations and respiratory mucosal injury and reflex bronchospasm) and cardiac dysfunction (OSA leads to cardiac dysfunction and CHF itself has been known to worsen asthma) [23][24][25][26].…”
Section: Discussionmentioning
confidence: 90%
“…This trend will represent an opportunity for the sleep field, for example treatment of OSA, which reduces perioperative complications, at least in some individuals . Similarly, addressing sleep disorders in congestive heart failure, diabetes, COPD and accelerated cognitive decline may serve to improve the wellbeing of these patients from the standpoint of quality of care and health outcomes …”
Section: Value‐based Purchasing and Quality Improvementmentioning
confidence: 99%